Fabrication and spectroscopic investigation of sandwich-like ZnO:rGO:ZnO:rGO:ZnO structure by layer-by-layer approach - Pandiyarajan, Thangaraj; Viswanathan Mangalaraja, Ramalinga; Karthikeyan, Balasubramanian; Arulraj, Arunachalam; Gracia Pinilla, Miguel Ángel (2023)
Transparent conducting materials (TCMs) are the heart of modern optoelectronic industries and the properties of TCMs could be improved by the introduction of 2D carbon materials. In this report, the influence of order layering on microstructural, transparency and emission characteristics of ZnO:rGO:ZnO:rGO:ZnO and rGO:ZnO:rGO:ZnO:rGO sandwich structures has been investigated. The layer-by-layer approach has been adopted for the fabrication of sandwich structured materials ZnO:rGO:ZnO:rGO:ZnO and rGO:ZnO:rGO:ZnO:rGO through the spin coating technique. The sandwich structures of ZnO and rGO exhibited hexagonal wurtzite structure of ZnO without any impurities were identified through XRD. The ordering of layer's influenced the microstructural parameters and were significantly altered. The spherical nature of the particles and the formation of the sandwich structures were confirmed by using SEM micrograph. The reduction in an optical transparency and narrowing bandgap of the ZnO upon the order of layering were identified through transmission spectra. The lower energy shift of near band edge (NBE) emission and reduction in the emission intensity with respect to pure ZnO nanostructures was observed. The present work provides a simple layer-by-layer approach to fabricating sandwich structures and improving the optical properties which have potential applications in various optoelectronic devices.